(untitled) (Majalah Kedokteran Bandung, 2020)
In pregnant women, cardiovascular complications are among the causes of maternal death, one of which is peripartum cardiomyopathy (PPCM). The similarity in the mechanism of PPCM and pre-eclampsia makes preeclampsia a risk factor for PPCM. Preeclampsia, together with PPCM, also contributes to the increasing maternal mortality when most of the causes of maternal death are preventable. This case study aimed to provide descriptions as the basis in education, raising public awareness, early detection, and early treatment, especially for patients at risk. Eight PPCM cases with preeclampsia were identified during the period of 2017–2018 in Dr. Hasan Sadikin General Hospital Bandung, Indonesia (RSHS). Cases of PPCM with preeclampsia are rarely reported in RSHS. Out of 8 patients, 7 experienced severe preeclampsia and 1 had impending eclampsia. Diagnosis in PPCM patients requires a complete history taking, physical examination, and other diagnostic tests such as echocardiography. In this study, all patients (100%) complained of dyspnea on exertion as a chief complaint and, based on the New York Heart Association in 1994, 87.5% were included in functional class III-IV. The average ejection fraction was shown to be 34.6%, indicating a value below normal limit. Studi Kasus Dekompensasi Jantung pada Pasien Preeklampsia dengan Kardiomiopati Peripartum Pada wanita hamil, komplikasi kardiovaskular berperan dalam kematian ibu, salah satunya adalah kardiomiopati peripartum (PPCM). Persamaan patogenesis antara PPCM dan pre-eklampsia menjadikan preeklampsia sebagai faktor risiko untuk PPCM. Preeklampsia bersama dengan PPCM berperan dalam peningkatan angka kematian ibu (AKI) ketika sebagian besar penyebab AKI dapat dicegah. Studi kasus ini bertujuan diharapkan untuk memberikan deskripsi sebagai dasar dalam pendidikan, meningkatkan kesadaran masyarakat, deteksi dini, dan perawatan dini, terutama untuk pasien yang berisiko. Pada tahun 2017–2018, terdapat 8 kasus pasien PPCM dengan preeklampsia yang dirawat di RSUP Dr. Hasan Sadikin Bandung (RSHS). Kasus PPCM dengan preeklampsia jarang dilaporkan di RSHS. Dari 8 pasien, 7 mengalami preeklamsia berat dan 1 mengalami eklampsia yang akan datang. Diagnosis pada pasien PPCM memerlukan anamnesis yang lengkap, pemeriksaan fisik, dan pemeriksaan penunjang seperti ekokardiografi. Pada penelitian ini, semua pasien (100%) mengeluhkan sesak nafas sebagai keluhan utama dan berdasar atas klasifikasi New York Heart Association tahun 1994, 87.5% termasuk dalam kelas fungsional III-IV. Rata-rata fraksi ejeksi menunjukkan 34.6% yang menandakan nilai di bawah batas normal.